2009
DOI: 10.1111/j.1439-0507.2009.01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different susceptibility testing methods and media on determination of the relevant fluconazole minimum inhibitory concentrations for heavy trailing Candida isolates with low-high phenotype

Abstract: We investigated the incidence of trailing growth with fluconazole in 101 clinical Candida isolates (49 C. albicans and 52 C. tropicalis) and tried to establish the convenient susceptibility testing method and medium for fluconazole minimum inhibitory concentration (MIC) determination. MICs were determined by CLSI M27-A2 broth microdilution (BMD) and Etest methods on RPMI-1640 agar supplemented with 2% glucose (RPG) and on Mueller-Hinton agar supplemented with 2% glucose and 0.5 μg ml(-1) methylene blue (GMB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…The type of medium i. e. composition, incubation times and temperature can influence the growth and detectability of fungi from the clinical samples and the MIC values of the tested strains (Als et al, 2010; Cruz et al, 2013; Balouiri et al, 2016). The Sabouraud and YEPD media are effective and most useful as media for subculture (Washington et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The type of medium i. e. composition, incubation times and temperature can influence the growth and detectability of fungi from the clinical samples and the MIC values of the tested strains (Als et al, 2010; Cruz et al, 2013; Balouiri et al, 2016). The Sabouraud and YEPD media are effective and most useful as media for subculture (Washington et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…22 Genetic resistance is mediated in C albicans by gainof-function mutations in the transcription factor Upc2, resulting in constitutive upregulation of Erg11, 23 and transcription factors are associated with mortality rates at least as high as those of more resistant species, such as C glabrata. 24,25 18,[27][28][29][30][31][32] Trailing growth was shown to be associated with upregulation of efflux transporter expression, 30,33 but not with azole resistance as determined using sterol quantitation. 28 No association was found between trailing and response to fluconazole treatment in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we measured susceptibility and tolerance in a broad range of clinical isolates spanning the major C. albicans clades 62-64 and asked how these parameters influence fungal infection outcomes. We analyzed disk diffusion assays using diskImageR , and quantified the radius (RAD) of the zone of inhibition, a parameter that relates to the MIC 65 , and the fraction of growth (FoG) within the zone of inhibition, a parameter that measures tolerance 19,38,50,66-68 . We found that a range of adjuvant drugs, used in combination with FLC, increased drug cidality by reducing FoG and not MIC and were effective both in vitro and in vivo at inhibiting strains with high (and not low) FoG levels.…”
Section: Introductionmentioning
confidence: 99%